Healthy-lifestyle behaviors associated with overweight and obesity in US rural children - Tovar Alison; Chui Kenneth; Hyatt Raymond R; Kuder Julia; Kraak Vivica I; Choumenkovitch Silvina F; Hastings Alia; Bloom Julia; Economos Christina D (BMC, 2012)
Abstract Background There are disproportionately higher rates of overweight and obesity in poor rural communities but studies exploring children's health-related behaviors that may assist in designing effective interventions are limited. We examined the association between overweight and obesity prevalence of 401 ethnically/racially diverse, rural school-aged children and healthy-lifestyle behaviors: improving diet quality, obtaining adequate sleep, limiting screen-time viewing, and consulting a physician about a child's weight. Methods A cross-sectional analysis was conducted on a sample of school-aged children (6-11 years) in rural regions of California, Kentucky, Mississippi, and South Carolina participating in CHANGE (Creating Healthy, Active, and Nurturing Growing-up Environments) Program, created by Save the Children, an independent organization that works with communities to improve overall child health, with the objective to reduce unhealthy weight gain in these school-aged children (grades 1-6) in rural America. After measuring children's height and weight, we17 assessed overweight and obesity (BMI ≥ 85th percentile) associations with these behaviors: improving diet quality18 (≥ 2 servings of fruits and vegetables/day), reducing whole milk, sweetened beverage consumption/day; obtaining19 adequate night-time sleep on weekdays (≥ 10 hours/night); limiting screen-time (i.e., television, video, computer,20 videogame) viewing on weekdays (≤ 2 hours/day); and consulting a physician about weight. Analyses were adjusted 21 for state of residence, children's race/ethnicity, gender, age, and government assistance. Results Overweight or obesity prevalence was 37 percent in Mississippi and nearly 60 percent in Kentucky. Adjusting for covariates, obese children were twice as likely to eat ≥ 2 servings of vegetables per day (OR=2.0,95% CI 1.1-3.4), less likely to consume whole milk (OR=0.4,95% CI 0.2-0.70), Their parents are more likely to be told by their doctor that their child was obese (OR=108.0,95% CI 21.9-541.6), and less likely to report talking to their child about fruits and vegetables a lot/sometimes vs. not very much/never (OR=0.4, 95%CI 0.2-0.98) compared to the parents of healthy-weight children. Conclusions Rural children are not meeting recommendations to improve diet, reduce screen time and obtain adequate sleep. Although we expected obese children to be more likely to engage in unhealthy behaviors, we found the opposite to be true. It is possible that these groups of respondent parents were highly aware of their weight status and have been advised to change their children's health behaviors. Perhaps given the opportunity to participate in an intervention study in combination with a physician recommendation could have resulted in actual behavior change.